Epimutations in Developmental Genes Underlie the Onset of Domestication in Farmed European Sea Bass. (10th July 2019) - Anastasiadi, Dafni; Piferrer, Francesc
Abstract: Domestication of wild animals induces a set of phenotypic characteristics collectively known as the domestication syndrome. However, how this syndrome emerges is still not clear. Recently, the neural crest cell deficit hypothesis proposed that it is generated by a mildly disrupted neural crest cell developmental program, but clear support is lacking due to the difficulties of distinguishing pure domestication effects from preexisting genetic differences between farmed and wild mammals and birds. Here, we use a farmed fish as model to investigate the role of persistent changes in DNA methylation (epimutations) in the process of domestication. We show that early domesticates of sea bass, with no genetic differences with wild counterparts, contain epimutations in tissues with different embryonic origins. About one fifth of epimutations that persist into adulthood are established by the time of gastrulation and affect genes involved in developmental processes that are expressed in embryonic structures, including the neural crest. Some of these genes are differentially expressed in sea bass with lower jaw malformations, a key feature of domestication syndrome. Interestingly, these epimutations significantly overlap with cytosine-to-thymine polymorphisms after 25 years of selective breeding. Furthermore, epimutated genes coincide with genes under positive selection in other domesticates. We argue that the initial stages of domestication include dynamic alterations in DNA methylation of developmental genes that affect the neural crest. Our results indicate a role for epimutations during the beginning of domestication that could be fixed as genetic variants and suggest a conserved molecular process to explain Darwin's domestication syndrome across vertebrates.